Food neophobia associates with lower dietary quality and higher BMI in Finnish adults - Knaapila Antti; Sandell Mari; Vaarno Jenni; Hoppu Ulla; Puolimatka Tuuli; Kaljonen Anne; Lagström Hanna (My University, 2022)
Objective: Food neophobia has been associated with decreased consumption of
vegetables mainly among children. We hypothesized that food neophobia in
adults is also associated with lower overall dietary quality and higher BMI.
Design: Data for the present cross-sectional analyses were derived from parents in
a follow-up family study.
Setting: The STEPS study, a longitudinal study of health and development of a
cohort of children born in south-west Finland.
Subjects: The parents, 1178 women (age 19–45 years, mean 32·2 years) and 1013
men (age 18–57 years, mean 34·1 years), completed a questionnaire at home
when their child was 13 months old. The questionnaire included the Food
Neophobia Scale (FNS; range 10–70), the Index of Diet Quality (IDQ; range 0–16)
and a measure of fruit and vegetable consumption. At that time the participants’
height and weight were also measured by a research nurse to calculate BMI.
Results: Compared with the food neophilics (FNS score 10–24), the food neophobics
(FNS score 40–70) consumed fewer vegetables (women: 15 v. 10 portions/week;
men: 13 v. 7 portions/week), scored lower on the IDQ (women: 9·7 v. 8·5; men: 8·8
v. 7·8) and had higher BMI (women: 24·2 v. 26·0 kg/m2; men: 26·5 v. 27·5 kg/m2) as
tested by one-way ANOVA, with all P values <0·001 in women and <0·05 in men.
The food neophobics followed a diet lower in nutritional quality than did the food
neophilics, especially regarding vegetables.
Conclusions: Food neophobia may complicate adaptation to dietary recommendations
and predispose to overweight.